2022
DOI: 10.1038/s41598-022-05732-8
|View full text |Cite
|
Sign up to set email alerts
|

Gas fields and large shallow seismogenic reverse faults are anticorrelated

Abstract: We investigated the spatial relationships among 18 known seismogenic faults and 1651 wells drilled for gas exploitation in the main hydrocarbon province of northern-central Italy, a unique dataset worldwide. We adopted a GIS approach and a robust statistical technique, and found a significant anticorrelation between the location of productive wells and of the considered seismogenic faults, which are often overlain or encircled by unproductive wells. Our observations suggest that (a) earthquake ruptures encompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…In a final step, the identified aquifers and depleted hydrocarbon fields were uploaded to a Geographical Information System (GIS) map, where we also plotted the location of potential sources of earthquakes larger than Magnitude 5.5 included in the Database of Individual Seismogenic Sources (DISS) of the Istituto Nazionale di Geofisica e Vulcanologia (INGV) [55]. Two studies that addressed the anti-correlation between the occurrence of gas reservoirs and large seismogenic faults in Italy [56,57] found that large earthquakes cause large slips over large faults compared to smaller events where the associated slip is too small to potentially affect reservoir integrity. Therefore, sites located over or near these larger seismogenic sources were not considered as favourable for UHS.…”
Section: Data Collection and Mappingmentioning
confidence: 99%
“…In a final step, the identified aquifers and depleted hydrocarbon fields were uploaded to a Geographical Information System (GIS) map, where we also plotted the location of potential sources of earthquakes larger than Magnitude 5.5 included in the Database of Individual Seismogenic Sources (DISS) of the Istituto Nazionale di Geofisica e Vulcanologia (INGV) [55]. Two studies that addressed the anti-correlation between the occurrence of gas reservoirs and large seismogenic faults in Italy [56,57] found that large earthquakes cause large slips over large faults compared to smaller events where the associated slip is too small to potentially affect reservoir integrity. Therefore, sites located over or near these larger seismogenic sources were not considered as favourable for UHS.…”
Section: Data Collection and Mappingmentioning
confidence: 99%
“…Penggunaan webgis saat ini telah berkembang untuk berbagai sektor seperti pemanfaatannya dalam pembangunan wilayah seperti smart city (Hari Ginardi et al, 2017), pendidikan, integrasi basis data biota laut (Agurto et al, 2018), integrasi dengan sistem cloud computing (De Lázaro Torres et al, 2017;Fortunato et al, 2017;Helmi et al, 2018;Piragnolo et al, 2021;Sciacca et al, 2022;Xia et al, 2015), kesehatan (Barik et al, 2019;Mooney & Juhász, 2020), bibliografi dalam penelitian (Howell et al, 2019), manajemen mitigasi kebencanaan (Capolupo et al, 2021;Fauzia et al, 2021;Feng et al, 2012;Franceschini et al, 2022;Gang et al, 2016;Gebreegziabher et al, 2021;Xianfu et al, 2012), forecasting (Fortunato et al, 2017), pariwisata (Klug et al, 2012), minyak dan gas bumi (Abdunaser, 2020;Khan & Hasan, 2020;Li, 2020;Russell et al, 2015;Valensise et al, 2022), hingga dalam memberikan solusi kebijakan dalam penentuan lokasi pembangkit listrik power to gas (La Guardia et al, 2021).Penggunaan perangkat lunak dalam bidang geospasial sangat disarankan sesuai dengan amanat UU No 11 Tahun 2011 tentang Informasi Geospasial pasal 31 yang menyatakan bahwa pengolahan data geospasial dan informasi geospasial dilakukan dengan perangkat lunak yang berlisensi dan/atau bersifat bebas dan terbuka (Mary Fargher, 2018;Serrano-Estrada et al, 2021).…”
Section: Pendahuluanunclassified
“…Initially considered a seismic gap (Burrato et al, 2008) within a single, continuous deformation front, since no major event occurred between the two strong historical events of 1695 and 1873 (see Figure 1), the MT was then segmented into smaller hypothetical faults; the potential sources of major earthquakes are now interpreted split in two sub-parallel fronts (see sources labeled ITCS060, ITCS105 and ITIS101 in the different versions of the database DISS, see Data Availability Section). Several authors now suggest a potential aseismic role of MT, considering the microseismic record (Romano et al, 2019), geodetic/seismic modeling (Barba et al, 2013), or analogs with other anticlines hosting productive gas reservoirs (Valensise et al, 2022).…”
Section: Introductionmentioning
confidence: 99%